Attacks of Kalotermes flavicollis Fabricius (1793) and Associated Aspergillus Micheli ex Haller (1768) Species - Giulia Mirabile; Livio Torta; Marika Lamendola; Maria Concetta Rizzo; Barbara Manachini (Insects)
The yellow-necked dry-wood termite Kalotermes flavicollis (Fabricius, 1793) (Blattodea: Kalotermitidae) is an important pest that infests wood in Europe. An increase in attacks by K. flavicollis has been seen in buildings and in churches in Palermo (Italy), with attacks on both structural elements and artefacts. Future climate changes are expected to lead to increasing temperatures, which will probably affect the pest status of this species, which is difficult to control. In this context, it is important to identify potential natural antagonists of K. flavicollis. During a survey of the K. flavicollis population, several dead individuals with evident fungal efflorescence were found. Therefore, a study aimed at the isolation and identification of these microorganisms was conducted. Fungal colonies isolated from mycelial structures grown on insects were identified based on morphological characteristics and DNA profiling. Three different species were identified: Aspergillus nomius, A. subramanianii, and A. tamarii. This is the first time that fungi have been recorded in association with the yellow-necked dry-wood termite and, in addition, this study reports the first association of A. subramanianii with Isoptera.